Poisoning - From Specific Toxic Agents to Novel Rapid and Simplified Techniques for Analysis 2017
DOI: 10.5772/intechopen.72006
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Risk Factors for Acute Pesticide Poisoning among Farmers in Asia

Abstract: Types of pesticides are used in farming to increase the productivity and protection of crops or to control pests. However, exposure to acute pesticide poisoning is one of the most important occupational risk factors among farmers all over the world. They are directly exposed to high levels of pesticide poisoning when involved in the handling, spraying, mixing, or preparing of it. The low educational level, lack of information, training, judgment or experience, and the inability to read on pesticide safety are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Acute toxic effects are easily recognized, whereas the effects resulting from long-term exposure to low doses are often difficult to distinguish. However, a growing evidence has confirmed that chronic exposure to pesticides may involve alterations of various organs and systems of the human organism such as the nervous, endocrine, immune, reproductive, renal, cardiovascular, and respiratory ones; therefore, an increase in risk is documented for multiple pathologies such as: cancer, diabetes, respiratory diseases, neurodegenerative diseases, cardiovascular diseases, disorders of the reproductive sphere, metabolic and hormonal dysfunction (thyroid), with different molecular implications [11,12]. Attention is payed to consequences for human health from ‘chronic’exposure to pesticides, i.e., exposure to small and prolonged doses over time whichdoes not concern only the population exposed toworking reasons, but it now concerns the whole general population [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Acute toxic effects are easily recognized, whereas the effects resulting from long-term exposure to low doses are often difficult to distinguish. However, a growing evidence has confirmed that chronic exposure to pesticides may involve alterations of various organs and systems of the human organism such as the nervous, endocrine, immune, reproductive, renal, cardiovascular, and respiratory ones; therefore, an increase in risk is documented for multiple pathologies such as: cancer, diabetes, respiratory diseases, neurodegenerative diseases, cardiovascular diseases, disorders of the reproductive sphere, metabolic and hormonal dysfunction (thyroid), with different molecular implications [11,12]. Attention is payed to consequences for human health from ‘chronic’exposure to pesticides, i.e., exposure to small and prolonged doses over time whichdoes not concern only the population exposed toworking reasons, but it now concerns the whole general population [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Many pesticides cause acute, chronic poisoning, and death in developing countries as toxic chemicals. [17][18][19] Poisoning of pesticides mainly occurs during preparation and application, such as mixing, loading, spraying, and cleaning the equipment. Hence, the agricultural workers mostly got chronic poisoning because they were repeatedly exposed to adverse health effects and death.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is less reporting of pesticide poisoning among farmers [ 15 ]. Furthermore, the status of protective measures and their effective determinants in a comprehensive study to reduce poisoning and exposure to pesticides is unclear [ 16 ]. Numerous cross-sectional studies have been conducted on the determinants of performing protective measures to reduce exposure to pesticides, but there is no systematic study that comprehensively examines the impact of these factors.…”
Section: Introductionmentioning
confidence: 99%